Haksız rekabet ile rekabetin korunması alanları arasındaki hukuki ilişki - Şenol, Pınar Uzun (My University, 2022)
Aynı kavram etrafında şekillenmiş haksız rekabet ile rekabet hukuku alanları, amaçları, korudukları menfaatler ve dayandıkları temel esaslar bakımından birbirinden farklıdır. Ancak bu farklılık, çatışma hâlinde olduklarını göstermez. Her ikisi de özgür ve dürüst rekabetin yasal dayanağı ve etkin rekabetin teminatıdır. Nitekim her iki disiplin etkin bir rekabetin sağlandığı piyasayı düzenlemekte birlikte görev edinmiştir. Bu sebeple rekabet yasaları birbirine paralel nitelik taşıyan düzenlemeler vasıtasıyla hem özgür hem de dürüst rekabet ortamını sağlamaya çalışır. Özgür rekabet ancak yasal sınırlar içinde, dürüstlük ilkesinin hâkim olduğu bir ekonomik düzen içerisinde mümkün olur. Bu durum her iki alanın her zaman karşılıklı etkileşim içinde olduğunun bir göstergesidir. Ayrı kanunlarda düzenlenen ve uygulama alanları da birbirinden farklılık gösteren bu iki bağımsız disipline, aynı anda, kendi yöntem ve korudukları menfaatler çerçevesinde başvurulur. Burada hakların yarışması kurumundan bahsedilmez. İki alanın örtüşmesi, zaman zaman etkileşim içinde olması, benzer konularda iki hukuk dalına da başvurulmasını mümkün kılar. Bu konulara ilişkin yapılan başvurularda, her iki hukuk dalı kendi yöntemleri ile olayı çözüme kavuşturur. Her iki disipline ait hükümler çelişkili bir şekilde uygulanamaz. Çünkü rekabetçi piyasa yapısı, ancak, rekabet hukuku ile haksız rekabet hükümlerinin birlikte uygulanabilmesiyle tam anlamıyla korunmuş olur. Haksız rekabet hükümleri, rekabet ortamını ortadan kaldıracak ya da rekabet kurallarını uygulanamaz hâle getirecek şekilde yorumlanmamalı ve rekabet serbestisini sınırlayıcı bir işlevde görülmemelidir. Öte yandan, rekabetçi piyasada rekabet hukuku ile tesis edilmeye çalışılan rekabet özgürlüğü de haksız rekabete izin verecek şekilde genişletilmemelidir.

The areas of unfair competition and competition law, which are shaped around the same concept, differ in terms of their aims, the interests they protect and the main principles on which they are based. However, this difference does not mean that they conflict. Both are the legal basis of free and fair competition and the guarantee of effective competition. As a matter of fact, both disciplines have taken on a task together in regulating the market where effective competition is ensured. For this reason, competition legislation try to provide both a free and fair competition environment through regulations that are parallel to each other. Free competition is possible only within legal limits, in an economic order dominated by the good faith principle. This is an indication that both fields are always in mutual interaction. These two independent disciplines, which are regulated in separate legislation and whose fields of application differ from each other, are applied simultaneously within the framework of their own methods and the interests they protect. The contest of rights institution does not take place here. The overlap of the two fields and their occasional interaction allow the application of both branches of law on similar issues. In the applications made on these issues, both branches of law resolve the case with their own methods. The provisions of both disciplines cannot be applied in a contradictory way since the competitive market structure can only be fully protected by the application of competition law and unfair competition provisions together. Unfair competition provisions should not be interpreted in a way that would eliminate the competitive environment or render the competition rules inapplicable and should not be perceived as limiting the freedom of competition. On the other hand, the freedom of competition, which is attempted to be established by competition law in the competitive market, should not be expanded to the extent that allows unfair competition.
Keywords: Civil law; Competition Law; Competition, Unfair; Competitive Market; Dürüst Rekabet; Fair Competition; Freedom of Competition; Haksız Rekabet; Hukuk; Law; Market Participants; Medeni hukuk; Piyasa Katılımcıları; Rekabet Hukuku; Rekabet Özgürlüğü; Rekabet Piyasası; Rekabet, Haksız; Unfair Competition